Current advances in the catalytic conversion of carbon dioxide by molecular catalysts: an update. Issue 38 (12th September 2018) - Tappe, Nadine A.; Reich, Robert M.; D'Elia, Valerio; Kühn, Fritz E.
Abstract : Recent advances (2015–) in the catalytic conversion of CO2 by metal-based and metal-free systems are discussed. Abstract : Due to the high emissions of CO2 and the related environmental impact, the chemical transformation of CO2 to useful industrially relevant products or their precursor is of significant interest. Recycling CO2 as a building block for the synthesis of chemicals may not only reduce further emission by at least replacing oil-derived feedstocks, but also provide the advantages of CO2 as an inexpensive, non-toxic and easily available substrate. The catalytic conversion of CO2 into small, useful molecules such as carbonates, methyl amines, methanol, formic acid, etc . by molecular catalysts is an interesting topic that has strongly developed in recent years. This review provides an overview of current scientific progress in the activation and conversion of carbon dioxide with industrially and scientifically relevant substrates using molecular catalysts. Metal-based catalysts are presented in the first part of the review whereas metal-free systems are described in the second part.